Introduction to Psychological First Aid, Obtaining Information About Children with Special Needs After Disaster and Crisis Situation - Kacan, Havva (Nobel Tip Kitabevleri, 2024)
Natural disasters are events that interrupt individuals, families, and society in many ways, especially economic and social life, in a short time, stop human activities, and cause great fi nancial losses, deaths, and injuries. Since it is not possible to predict where, when, how, and to what extent disasters such as earthquakes will aff ect them, they especially aff ect individuals with special needs, their parents, and their close circle. Psychological fi rst aid becomes important for children with special needs and their families in situations such as disasters and crises. Special precautions need to be taken in order to minimize the impact of children with special needs on the negative eff ects of disasters. Th is section aims to discuss the concept of psychological fi rst aid within the scope of children with special needs and make suggestions. Th ere are no standard practices for children with special needs and their families in our country. Emphasis was placed on collecting and recording information from individuals, ethical principles, and security skills that private individuals can acquire.